Authenticity, transition and mathematical competence: an exploration of the values and ideology underpinning an increase in the amount of mathematics in the science curriculum in England - Wong, V (Taylor and Francis, 2019)
Science is a much-revised and contested area of the curriculum. A new curriculum has recently been introduced in England which includes far more mathematical aspects of science than previous versions. This study asks what the influences, ideologies and values are which led to this change. A two-phase qualitative approach was followed comprising semi-structured interviews with key contributors to the science and mathematics education discourse together with an analysis of government and other influential documentation. This study is unusual both in its focus on those who were responsible for making science education policy and its focus on the policy development of the mathematical aspects of the science curriculum. The findings suggest that drivers for increasing the amount of mathematics in science include concerns about standards, the difficulties students have transitioning to higher stages of science education and the desire to improve students’ broader mathematical competence. Aiming to improve students’ mathematical competence is an aim for all students. In contrast, helping students transition to further scientific study is for a minority. I argue that ideologies and values which underpin the curriculum need to be interrogated more closely and should remain a focus of research.